2003
DOI: 10.1128/aem.69.4.2133-2138.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages ofErwinia amylovora

Abstract: Fifty bacteriophage isolates of Erwinia amylovora, the causal agent of fire blight, were collected from sites in and around the Niagara region of southern Ontario and the Royal Botanical Gardens, Hamilton, Ontario. Forty-two phages survived the isolation, purification, and storage processes. The majority of the phages in the collection were isolated from the soil surrounding trees exhibiting fire blight symptoms. Only five phages were isolated from infected aerial tissue in pear and apple orchards. To avoid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 14 publications
6
106
1
3
Order By: Relevance
“…Despite a 1998 study specifically assessing the prevalence of broad-host-range phages (Jensen et al, 1998), and recent examples of such phages in Gram-positive genera (Ammann et al, 2008;Chen & Novick, 2009), the consensus remains that phage infection tends to be species and strain specific. However, other examples of broad-host-range phages have been reported (for example, see Gill et al, 2003), and such a stringent model of phage-bacterium interactions fails to explain the abundance of phages in the environment. Neither of the bacterial strains used in this study has been genomically sequenced, and the P. agglomerans strain has not been characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a 1998 study specifically assessing the prevalence of broad-host-range phages (Jensen et al, 1998), and recent examples of such phages in Gram-positive genera (Ammann et al, 2008;Chen & Novick, 2009), the consensus remains that phage infection tends to be species and strain specific. However, other examples of broad-host-range phages have been reported (for example, see Gill et al, 2003), and such a stringent model of phage-bacterium interactions fails to explain the abundance of phages in the environment. Neither of the bacterial strains used in this study has been genomically sequenced, and the P. agglomerans strain has not been characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Several phages affecting E. amylovora strains were found (Schnabel and Jones 2001;Gill et al 2003). They differed in genome size and restriction patterns as well as in host range.…”
Section: Host Range and Virulencementioning
confidence: 99%
“…Ritchie and Klos [55,56] used a single host strain for isolation of phages and reported that the tested E. amylovora phages isolated from aerial parts of apple trees had a narrow host range, as they were able to lyse only isolates of E. amylovora and the closely related saprophyte, P. agglomerans. On the other hand, Gill et al [57] found that phages isolated using a mixture of multiple host strains had a broader host range. During our own investigations, we used several Hungarian E. amylovora strains for the isolation of phages (Schwarczinger and Kolozsvári Nagy, unpublished data).…”
Section: Isolation Of Phagesmentioning
confidence: 99%
“…The authors found that these phages were highly specific to E. amylovora. In 2003, Gill et al [57] estimated the diversity of bacteriophages collected from orchards in southern Ontario and reported the detailed characteristics of various sets of phages with broad host ranges. Forty-two phage isolates were identified within six distinct phage types based on molecular characterization of the phages using a combination of PCR and restriction endonuclease digestions.…”
Section: Molecular Characterization Of Phagesmentioning
confidence: 99%
See 1 more Smart Citation